From socialization to internalization: tracing knowledge co-construction through sequential discourse interaction acts in high school English learning - Wu, Yongwen; Kanji, Mahapiret; Ou, Guang'an (Frontiers in Education, 2025)
IntroductionEffective knowledge co-construction (KC) leading to deep internalization remains a critical challenge in high school English as a Foreign Language (EFL) instruction. While classroom discourse is central to this process, the specific sequential mechanisms linking teacher-student interactions to knowledge internalization are underexplored. This study aims to: (1) identify distinct patterns of classroom discourse sequences, differentiating high- and low-quality interactions, and (2) elucidate teachers' scaffolding role in language KC within the SECI (Socialization, Externalization, Combination, Internalization) knowledge creation model.MethodsEmploying an explanatory sequential mixed-methods design within a social-cognitive framework, we video-recorded 56 naturally occurring whole-class EFL lessons across three Chinese senior high schools. Generalized Sequential Querier (GSEQ) software was used to identify and quantitatively analyze 369 discourse interaction sequences for sequential patterns. Subsequent qualitative analysis focused on interpreting the scaffolding mechanisms within these sequences.ResultsAnalysis revealed distinct sequential patterns: low-quality interactions were characterized by fragmentation during the socialization and externalization phases, while high-quality interactions exhibited a cohesive spiral structure in the combination and internalization phases. Crucially, sequential analysis pinpointed teachers' pivotal scaffolding role via specific discourse acts throughout the SECI process: contextualized inquiries and cognitive conflicts ignited socialization; metacognitive questioning drove externalization; integrative tasks facilitated combination; and structured practice sequences supported internalization.DiscussionThis study elucidates the sequential mechanisms of KC, demonstrating how teacher-guided discourse scaffolding fundamentally transforms classroom interaction into deep language knowledge internalization. The findings provide a concrete, empirically-grounded framework for understanding and improving the micro-dynamics of KC in EFL classrooms, offering valuable insights for teacher professional development and the design of more effective discourse-based instructional strategies.